TRIM56 impairs HBV infection and replication by inhibiting HBV core promoter activity - Xing Tian; Huijun Dong; Xinyuan Lai; Guomin Ou; Junning Cao; Jihang Shi; Chengang Xiang; Lei Wang; Xuechao Zhang; Kai Zhang; Ji Song; Juan Deng; et al. (Antiviral Res ., 2022)
Members of the tripartite motif (TRIM) protein family strongly induced by interferons (IFNs) are parts of the innate immune system with antiviral activity. However, it is still unclear which TRIMs could play important roles in hepatitis B virus (HBV) inhibition. Here, we identified that TRIM56 expression responded in IFN-treated HepG2-NTCP cells and HBV-infected liver tissues, which was a potent IFN-inducible inhibitor of HBV replication. Mechanistically, TRIM56 suppressed HBV replication via its Ring and C-terminal domain. C-terminal domain was essential for TRIM56 translocating from cytoplasm to nucleus during HBV infection. Further analysis revealed that TRIM56's Ring domain targeted IκBα for ubiquitination. This modification induced phosphorylation of p65, which subsequently inhibited HBV core promoter activity, resulting in the inhibition of HBV replication. The p65 was found to be necessary for NF-κB signal pathway to inhibit HBV replication. We verified our findings using HepG2-NTCP and primary human hepatocytes. Our findings reveal that TRIM56 is a critical antiviral immune effector and exerts an anti-HBV activity via NF-κB signal pathway, which is essential for inhibiting transcription of HBV covalently closed circular DNA.